2021
DOI: 10.1186/s13014-021-01826-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with multi-disciplinary management of central lung tumors with CT-guided percutaneous high dose rate brachyablation

Abstract: Background Centrally located lung tumors present treatment challenges given their proximity to mediastinal structures including the central airway, esophagus, major vessels, and heart. Therapeutic options can be limited for medically inoperable patients, particularly if they have received previous thoracic radiotherapy. High dose rate (HDR) brachyablation was developed to improve the therapeutic ratio for patients with central lung tumors. The purpose of this study is to report initial safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Comparing our results to those obtained by other authors describing the application of palliative endoscopy procedures such as laser therapy, electrocautery, diathermy, electrocoagulation, phototherapy, cryotherapy, endobronchial stent insertion, and combinations of these techniques, similar results have been obtained regarding the OS of the patients with a central airway obstruction (CAO) [20][21][22][23]. Future comparisons with stereotactic body radiotherapy and other ablative techniques are warranted to expand multi-disciplinary management options [24].…”
Section: Discussionsupporting
confidence: 81%
“…Comparing our results to those obtained by other authors describing the application of palliative endoscopy procedures such as laser therapy, electrocautery, diathermy, electrocoagulation, phototherapy, cryotherapy, endobronchial stent insertion, and combinations of these techniques, similar results have been obtained regarding the OS of the patients with a central airway obstruction (CAO) [20][21][22][23]. Future comparisons with stereotactic body radiotherapy and other ablative techniques are warranted to expand multi-disciplinary management options [24].…”
Section: Discussionsupporting
confidence: 81%
“…Secondary treatment options for isolated primary tumor site progression after SBRT include salvage lung resection, re-irradiation with external beam radiation therapy (EBRT), or percutaneous ablative procedures (cryotherapy, microwave ablation, radio-frequency ablation) [ 6 , 7 ]. A more novel approach is percutaneous high-dose-rate (HDR) brachyablation that is a minimally invasive treatment involving implantation of temporary catheters into lung tumors to deliver high doses of radiotherapy in a single fraction with minimal exposure of previously irradiated tissues [ 8 , 9 ].…”
Section: Purposementioning
confidence: 99%
“…Eleven published studies met the inclusion criteria in assessing the efficacy of single-fraction high-dose brachytherapy for cancers other than prostate, breast, and liver. The studies were published by groups in the following locations: 4 from the USA, 3 from Germany, 1 from Italy, 1 from the United Kingdom, 1 from China, and 1 from Spain [43][44][45][46][47][48][49][50][51][52][53]. Table 4 summarizes the oncological outcomes and toxicities for these eleven publications.…”
Section: Other Cancersmentioning
confidence: 99%
“…Amongst these studies, lung appears to have promising data. Yoon et al reported on 23 patients treated with 21.5 Gy single-fraction HDR brachytherapy, with local control of 96% at 2 years for centrally located primary and metastatic lung cancer, and no G3 or higher toxicities were reported [52]. Xiang et al also reported on single-fraction HDR lung brachytherapy in a phase I clinical trial.…”
Section: Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation